The influences of ICT development, globalization and socioeconomic factors on quality of governance and control of corruption in the ASEAN region / Darusalam - Darusalam (2022)
Since its establishment in 1967, ASEAN1 has made tremendous achievements in promoting peace, stability and in improving its socio-economic development. These have contributed towards the gradual increase in international trades, resulting in higher cumulative Gross National Product (GDP) for the region. However, recent business reports, white papers, and business conference proceedings have claimed that ASEAN’s progress in enhancing an integrated region has been constrained by key challenges such as poor governance and corruption. Review of previous studies has seen limited empirical evidence that support such earlier claims. As such, this study was undertaken to provide evidence on factors that influence poor governance and corruption in ASEAN. Premised on the key parameters of ASEAN’s three integration initiatives and the review of global studies, this study aimed to examine the influences of three variables, namely ICT development and globalization (as independent variables) and socioeconomic factors (as control variables) on two dependent variables, quality of governance (QoG) and control of corruption (CoC). Constrained by the availability of data, the study covered eight ASEAN member countries namely Indonesia, Malaysia, Thailand, Singapore, Philippines, Brunei Darussalam, Vietnam, and Myanmar. Panel data covering between 22 to 34 observational years for all the related variables were sourced from three trusted and reputable databases – The World Bank (for data on control of corruption and socio-economic factors), KOF Swiss Economic Institute (for data on ICT development and globalisation) and Quality of Government Institute, Gothenburg University of Sweden (for data on quality of governance). This study employed the Autoregressive Distributed Lag (ARDL) technique to assess the relationships between variables using two research frameworks. The information asymmetry and the social contract theories were utilized to explain the relationships between the variables. In the first research framework, it was found that ASEAN’s existing ICT development focussed mainly on ICT access and usage and lacked focus on ICT skills. This had resulted in a negative significant long-run relationship between ICT development and QoG. Similarly, the current interest in forging an intra-ASEAN globalization agenda was also found to be counter productive on QoG. In the second research framework, the study examined if there were relationships between ICT development and globalization with CoC. Interestingly, the long-run relationships between ICT development and CoC were showing positive and significant results, implicating that, ICT have been used effectively by users to report corruption. Many anti-corruption agencies in ASEAN are also found to be moving towards the digitalisation technology to detect and mitigate corruption. The enhancement of ICT skills at both the public and public sectors is an important strategy to be incorporated into the ASEAN ICT Masterplan. Moving the globalization agenda from merely focusing on intra-ASEAN partnership to building international economic and political collaborations with other developed non-ASEAN nations is seen as a necessary step to move ASEAN forward to another level. The long-run relationship between globalization and CoC also showed a positive significant result. The research contributions from this study can be viewed from four perspectives. First, contribution to practice includes the specific recommendations on ICT skills and diverse globalization policy to improve the QoG and CoC for ASEAN. Second, contribution to theory is in the use of the information asymmetry and the social contract theories to explain the knowledge gap between the citizens and the government, which resulted in the wrong interpretations of information and in the non-compliant of regulations related to governance and corruption. Third, contribution to methodology is through the incorporation of country-level macroeconomic data and analysis to financial and accounting research in governance and corruption studies. The document analysis of relevant reports enriched the descriptive statistical analysis of the study. Finally, contribution to the body of knowledge is through several published articles from this study, which have added towards the empirical findings and specific literature on the influence of ICT development and globalization on QoG and CoC in ASEAN.